Al solubility in (Ti1−cAlc)NiSn half-Heusler alloy. Issue 14 (21st March 2019) - Rabin, Daniel; Fuks, David; Gelbstein, Yaniv
Abstract : A combination of CALPHAD and ab initio DFT calculations with an experimental validation was carried out to study the Al solubility in TiNiSn. Abstract : Half-Heusler, HH, alloys are widely used n-type materials in thermoelectric applications. Today, there is a shortage in p-type HH based materials, which may have an inherent compatibility with the HH n-type pair. Al is a good candidate as an acceptor doping element for this purpose, and the results on alloying of TiNiSn-based HH with Al are reported in details. Combination of CALPHAD and ab initio DFT calculations with an experimental validation was carried out. It is demonstrated that low level Al doping leads to p-type conductivity of the material. The solubility of Al was predicted by calculations and experimentally confirmed. The stable phases with compositions above the solubility limit of Al were determined, including an assessment of the maximal Al solubility in the HH (Ti1− c Al c )NiSn phase up to 1400 K. In addition, a Scheil solidification simulation with the known TiNiSn CALPHAD database was used, in order to further understand the as-cast phase structure. It is shown that beyond the solubility limit the stable phases at room temperature are TiNiSn(HH), Sn(BCT) and NiAl(B2). The maximal solubility of Al in the HH phase is estimated as ∼1 at% at 1400 K. These results give the basic route for designing of (Ti1− c Al c )NiSn as a p-type thermoelectric element.